2022
DOI: 10.3390/ijms23137048
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between cGMP and Calcium Signaling in Alzheimer’s Disease

Abstract: Cyclic guanosine monophosphate (cGMP) is a ubiquitous second messenger and a key molecule in many important signaling cascades in the body and brain, including phototransduction, olfaction, vasodilation, and functional hyperemia. Additionally, cGMP is involved in long-term potentiation (LTP), a cellular correlate of learning and memory, and recent studies have identified the cGMP-increasing drug Sildenafil as a potential risk modifier in Alzheimer’s disease (AD). AD development is accompanied by a net increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 219 publications
0
6
0
1
Order By: Relevance
“…4D ). Both ATP2A3 and ITPR1 were involved in the cGMP and calcium signaling pathway, which was reported to be deregulated in AD patients and mouse models [ 23 ]. CLEC2L was reported to be downregulated in the entorhinal and temporal lobe cortex in AD patients [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…4D ). Both ATP2A3 and ITPR1 were involved in the cGMP and calcium signaling pathway, which was reported to be deregulated in AD patients and mouse models [ 23 ]. CLEC2L was reported to be downregulated in the entorhinal and temporal lobe cortex in AD patients [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there have been increasing investigations of electrically stimulated LTP observed at inhibitory synapses in different brain areas, including the hippocampus, although most are observed at excitatory synapses previously [ 93 ]. Researchers have demonstrated that excitatory LTP provides a more effective detection, while iLTP maintains the temporal resolution of the neuronal network by using a whole-cell patch clamp [ 94 ]. It means that the excitatory LTP is dominant for short stimulation intervals due to significant increases in spike generation.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ /calmodulin regulates constitutive expression types of the NOS family [ 92 ], confirming a possible connection to LTP and iLTP induction. Meanwhile, behavioral studies show that the NO/cGMP plays a role in learning and memory [ 93 , 94 ] because NO donors, l-Arginine, or cGMP analogs enhanced memory, whereas NOS inhibitors or genetic deletion hampered various types of memory [ 93 ].…”
Section: Ltp Mechanisms Of Excitatory and Inhibitory Synapsesmentioning
confidence: 99%
“…The role of NO-cGMP signaling in RGCs appears to be multifaceted. In CNS neurons, NO-cGMP signaling is important in NVC, synaptic plasticity, and synaptic transmission [ 107 ]. GC1 is expressed in pre- and post-synaptic terminals and in neuronal soma and spines [ 107 , 108 ].…”
Section: No-cgmp Signaling In Retinal Neuronsmentioning
confidence: 99%
“…In CNS neurons, NO-cGMP signaling is important in NVC, synaptic plasticity, and synaptic transmission [ 107 ]. GC1 is expressed in pre- and post-synaptic terminals and in neuronal soma and spines [ 107 , 108 ]. GC1 is also evident in RGC soma in the retina [ 26 ].…”
Section: No-cgmp Signaling In Retinal Neuronsmentioning
confidence: 99%